EXPERIENCE OF APPLICATION OF FINE-GRAINED TITANIUM NICKELIDE FOR THE TREATMENT OF BONE CYSTS IN CHILDREN - Слизовский, Григорий Владимирович; Кужеливский, Иван Иванович; Сигарева, Юлия Андреевна; Лисицкий, Николай Сергеевич; Ульянов, Владимир Владимирович; Ненашева, Дарья Владимировна (Mother and Baby in Kuzbass, 2019)
60 patients with dystrophic bone cysts were included in the study, where 30 of them underwent an original operation of bone grafting with finely granulated titanium nickelide. Clinical and radiological effectiveness of this method of treatment in the early rehabilitation period and with remote monitoring was demonstrated. The clinical effect was characterized as good in 96,6 % of patients during the observation period. Clinical experience shows that the application of the method of treatment of dystrophic bone cysts through plastics with titanium nickelide granules gives more positive results in comparison with the traditional method.